Type I hypersensitivity promotes Aedes aegypti blood feeding - Michael J. Conway (Nature Portfolio, 2021)
Abstract Mosquitoes play a major role in human disease by serving as vectors of pathogenic microorganisms. Mosquitoes inject saliva into host skin during the probing process. Mosquito saliva contains a number of proteins that facilitate blood feeding by preventing hemostasis. Mosquito saliva also contains potent allergens that induce type I hypersensitivity reactions in some individuals. Type I hypersensitivity reactions in skin involve IgE-mediated degranulation of mast cells, which leads to vasodilation and an itch sensation. We hypothesized that hypersensitivity to mosquito saliva influences blood feeding. To test this hypothesis, we recruited human subjects who consented to Aedes aegypti bites. We measured their first sensation of itch, the strength of their itch sensation, the number of times mosquitoes attempted to feed, the number of times mosquitoes probed their skin, feeding time, engorgement status, and wheal diameter. Here we show that hypersensitive subjects had a stronger itch sensation, and that the time to first itch sensation was inversely correlated with wheal diameter; however, mosquitoes tended to probe less and engorge more on these subjects. Follow-up experiments testing the impact of oral antihistamine treatment on mosquito feeding parameters failed to reveal a statistically significant result. Histamine also failed to promote blood feeding on an artificial membrane feeder. This study suggests that mosquito saliva-induced type I hypersensitivity promotes blood feeding but that this may be independent from histamine or histamine signaling.